2018
DOI: 10.1136/oemed-2017-104812
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer mortality and exposure to synthetic metalworking fluid and biocides: controlling for the healthy worker survivor effect

Abstract: Findings suggest a modest positive association for synthetic MWF with lung cancer mortality, contrary to the negative associations reported in earlier studies. Biocide exposure, however, was inversely associated with risk of lung cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A series of results from exposure-response analyses have also been reported based on the extensive historical exposure assessment for straight, soluble and synthetic MWF. Results based on Cox proportional hazard models for digestive and respiratory cancer mortality in relation to MWF exposures have been largely null (11)(12)(13)(14)(15). However, results based on cancer incidence in this cohort have been more mixed.…”
mentioning
confidence: 78%
“…A series of results from exposure-response analyses have also been reported based on the extensive historical exposure assessment for straight, soluble and synthetic MWF. Results based on Cox proportional hazard models for digestive and respiratory cancer mortality in relation to MWF exposures have been largely null (11)(12)(13)(14)(15). However, results based on cancer incidence in this cohort have been more mixed.…”
mentioning
confidence: 78%
“…Investigators dismiss the g-null paradox when they find nonnull effect estimates if substantive knowledge or prior studies suggested that the sharp causal null (condition 3) does not hold (e.g., see Refs. [13][14][15] ) or when they find null effect estimates precisely because, despite the potential for the existence of the g-null paradox, they do find a null result (e.g., see Ref. 16 ).…”
Section: Beyond the Sharp Causal Null Hypothesismentioning
confidence: 99%
“…The possibility of the g-null paradox is often handled informally in practice. Investigators dismiss the g-null paradox when they find non-null effect estimates if substantive knowledge or prior studies suggested that the sharp causal null (condition 3) does not hold (e.g., see [10,11,12]) or when they find null effect estimates precisely because, despite the potential for the existence of the g-null paradox, they do find a null result (e.g., see [13]).…”
Section: Beyond the Sharp Causal Null Hypothesismentioning
confidence: 99%